Negative impact of chemotherapy on kinetic growth rate of the future liver remnant if applied following PVE or ALPPS. - Klara Welcker; Martin A Schneider; Tim Reese; Andrea Ehrenfeld; Hauke Weilert; Axel Stang; Peter Wohlmuth; Mia-Maria Warnke; Carolin Reiner; Thomas von Hahn; Karl J Oldhafer; Andreas H Mahnken; et al. (PLoS ONE)
Purpose Modern liver surgery has improved the percentage of potentially resectable malignant tumors. However, if the future liver remnant is small, patients remain at risk of developing postoperative liver failure. Thus, the future liver remnant must be increased, while at the same time, the primary tumor may have to be controlled by chemotherapy. To address this conflict, we retrospectively analyzed the changes in hypertrophy before and after Associating Liver Partition with Portal vein ligation for Staged hepatectomy (ALPPS) or Portal Vein Embolization (PVE), with or without parallel systemic chemotherapy. Materials and methods We retrospectively analysed 172 patients (54 female and 118 male), treated with ALPPS in 90 patients (median age 61 years [Q1, Q3: 52,71]) and with PVE in 82 patients (median age 66 years [Q1, Q3: 56,73]). The median control interval was 4.9 [Q1, Q3: 4.0, 6.0] weeks after the PVE, and 2.6 [Q1, Q3: 1.6, 5.8] weeks after ALPPS step 1. Results The overall kinetic growth rate (median) for the entire group was 0.02 (2%) per week. When systemic chemotherapy was administered prior to intervention, the kinetic growth rate of these treated patients (vs. untreated) exhibited a median of 0.020 [Q1, Q3: 0.011, 0.067] compared to 0.024 [Q1, Q3: 0.013, 0.041] (p = 0.949). When chemotherapy was administered after the PVE/ ALPPS treatment, the kinetic growth rate declined from a median of 0.025 [Q1, Q3: 0.013, 0.053] to 0.011 [Q1, Q3: 0.007, 0.021] (p = 0.005). Subgroup analysis showed statistically significant effects only in the PVE group (median ALPPS -45% (p = 0.157), PVE -47% (p = 0.005)). Conclusion This retrospective analysis indicated that systemic chemotherapy given after PVE/ the first step of the ALPPS procedure, i.e., the growth phase, has a negative effect on the kinetic growth rate.